2011
DOI: 10.1111/j.1742-1241.2011.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

It’s good to talk! Changes in coronary revascularisation practice in PCI centres without onsite surgical cover and the impact of an angiography video conferencing system

Abstract: Summary Introduction:  Percutaneous coronary intervention (PCI) activity has increased more than 6 fold in the last 15 years. Increased demand has been met by PCI centres without on‐site surgical facilities. To improve communication between cardiologists and surgeons at a remote centre, we have developed a video conferencing system using standard internet links. The effect of this video data link (VDL) on referral pattern and patient selection for revascularisation was assessed prospectively after introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Additionally, the recent COVID‐19 pandemic has highlighted the need for video conferencing technology to enable teams to work together remotely. A previous study has shown that, using the video conferencing described MDTs are robust and clinically effective 12 . This study shows that they are also highly cost‐efficient.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, the recent COVID‐19 pandemic has highlighted the need for video conferencing technology to enable teams to work together remotely. A previous study has shown that, using the video conferencing described MDTs are robust and clinically effective 12 . This study shows that they are also highly cost‐efficient.…”
Section: Discussionmentioning
confidence: 52%